Efek Mediasi Organizational Citizenship Behavior diantara Kecerdasan Emosional dan Kecerdasan Spiritual terhadap Kinerja Tenaga Kependidikan Universitas Negeri Malang - Arifin, Fatikha Floressya (Jurnal Ilmiah Administrasi Publik, 2019)
The aim of this study was to explain the mediating effects of Organizational Citizenship Behavior (OCB) between emotional intelligence and spiritual intelligence on the performance of educational staff at the State University of Malang. In addition, this research is also aims to determine the extent of the influence of these three variables on performance. This type of research is quantitative with a survey method carried out for education staff at the State University of Malang. The sampling technique is proportional random sampling. The results showed that there was a partial mediating effect between emotional intelligence and spiritual intelligence on the performance of educational staff at the State University of Malang. The three variables also have a significant effect on the performance of education staff at State University of Malang.